ANALISIS ISI PADA PROGRAM DESTA AND GINA IN THE MORNING PADA RADIO PRAMBORS JAKARTA - Laurencia Laurencia; Sugeng Wahjudi (SEMIOTIKA: Jurnal Komunikasi, 2019)
ABSTRACTThis thesis is entitled "Analysis of the Contents of the Desta and Gina in the Morning Program on Prambors Jakarta radio" in accordance with the main problem formulation raised "How is the analysis of the contents of the Desta and Gina in The Morning program on Radio Prambors based on radio infotainment categories? And what is the editorial policy in the Desta and Gina in The Morning program based on the packaging of the contents inside? ". The purpose of this study is to determine the content of the analysis contained in the air magazine program Desta and Gina in The Morning on Prambors radio and to find out the editorial policy of the program applied to the Desta and Gina in The Morning program based on the contents of the information. The method used in this research is to use a quantitative data analysis method with a descriptive approach. By using descriptive technical analysis of the content that is calculated internally on the frequency and percentage based on existing categories. Based on his assessment, the results of the study were divided into three categories, based on Info-entertainment, Infotainment, and Information and entertainment. All three have different indicators. The conclusion of this research is that by looking at the editorial method in packaging, this program is neatly packaged and very attractive, so that it is interested by ad owners, interested listeners in participating through interactive events, having reliable sources of information with talkshows held.Keywords: Content Analysis, Editorial Policy, Radio Prambors ABSTRAKSkripsi ini berjudul “Analisis Isi Program Desta and Gina in the Morning pada radio Prambors Jakarta” sesuai dengan pokok rumusan masalah yang diangkat “Bagaimana analisis isi program Desta and Gina in The Morning di Radio Prambors berdasarkan kategori infotainment radio? Dan Bagaimana kebijakan redaksi dalam program Desta and Gina in The Morning berdasarkan pada pengemasan isi yang ada didalamnya?”. Tujuan dari penelitian ini adalah Untuk mengetahui konten analisis yang terkandung dalam program majalah udara Desta and Gina in The Morning di radio Prambors dan Untuk mengetahui kebijakan redaksi program yang diterapkan pada program Desta and Gina in The Morning berdasarkan isi informasinya. Metode yang digunakan dalam penelitian ini adalah menggunakan metode analisis data kuantitatif pendekatan deskriptif. Dengan menggunakan teknis analisis isi dekriptif yang perhitungannya secara interfal pada frekuensi dan presentase berdasarkan kategori yang ada. Berdasarkan penilaiannya, hasil penelitian dibagi kedalam tiga kategori, berdasarkan Info-entertainment, Infotainment, dan Information and entertainment. Ketiganya memiliki indikator yang berbeda. Kesimpulan dari penelitian ini adalah Melihat cara redaksi dalam pengemasan, program ini dikemas rapi dan sangat menarik, sehingga diminati oleh pemilik iklan, diminati pendengar dalam berpartisipasi melalui interaktif yang dibuka, memiliki sumber informasi terpercaya dengan perbincangan (talkshow) yang diadakan.Kata kunci: Konten Analisis, Kebijakan Redaksi, Radio Prambors